Desenvolvimento de uma impressora 3D com extrusão de chocolate - Ricci, Cristiane Pereira (Universidade Federal de São Carlos, 2021)
Additive manufacturing is a manufacturing process that allows obtaining complex shapes and/or with many stages. Therefore, obtaining a solid is a harder and more complex task. Historically, the use of this technique has started with printing polymers and in metallurgical industry. Currently, due to technological advances and cost reduction of components, the domestic and services markets have been reached, while the niche of custom gifts is promising. In this context, the cooking segment shows potential applications to chocolates and candies, given the current restrictions due to usage of molds. The use of additive manufacturing, through 3D printers, brings to the market new design options, making the final product innovative, competitive and customized, being these characteristics the motivation for the development of this academic work. The theme of this project is the development of a tridimensional printing device applied to the chocolate market. As part of the development of a system based on an open source printer already widely used for polymers, this project executed the necessary adaptations for use of this material, since the most relevant working parameters diverge from those seen on most common raw materials used by general industry. The solidification of chocolate can occur on several ways, affecting the final result of the parts, which may fall apart or fail to keep the desired geometry, being this one of the main challenges to the usage of this material. Key words: Additive Manufacturing; 3D Printing; Chocolate; Food; FDM
Project and development of a 3D printer extruding chocolate
Keywords: Manufatura aditiva; Impressão 3D; Alimentos; Chocolate; FDM; Additive manufacturing; 3D printing; Food; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO